An exploratory picture of the iranian mtDNA landscape - S. Farjadian; M. Sazzini; S. Tofanelli; L. Castrì; L. Taglioli; D. Pettener; A. Ghaderi; G. Romeo; D. Luiselli (Journal of Biological Research, 2012)
-